PEKERJAAN SEBAGAI FAKTOR PROTEKTIF MEMORI PADA LANSIA - Suwito, Michelle Margaretha; Handajani, Yvonne Suzy; Turana, Yuda; Kristian, Kevin (PERDOSNI, 2024)
Introduction: The risk of memory impairment increases with age, with a global prevalence of 20% of elderly experiencing difficulties in memory related activities.Aim: The aim of this study is to understand memory impairment and its associated factors in a community- dwelling setting in Kebon Jeruk, West Jakarta.Method: This cross-sectional study involved 98 participants aged over ≥60 years. Data was collected by interview using validated instruments. Statistical analysis was done using chi-square method for bivariate analysis and multiple logistic regression for multivariate analysis.Result: Majority of participants were women (71%), with ages of ≥65 years (81%), an education of >12 years (90%) and were unemployed (87%). Memory impairment was found in 82% of participants. Chi- square analysis showed that factors significant to memory impairment were age (p: 0.021; OR: 0.734; 95%CI: 0.515 – 1.046), occupation (p: 0.045; OR: 0.727; 95%CI: 0.486 – 1.127), and physical activity (p: 0.013; OR: 1.338; 95%CI: 0.998 – 1.794). Multiple logistic regression analysis showed that the most significant factor affecting memory impairment was age (OR: 3.766).Discussion: Memory impairment in the elderly is associated with age, occupation, and physical activity. Of these factors, age is the most significant factor, with a risk increase of 3.766 times in impairing memory of the elderly.Keywords: Age, elderly, memory impairment, occupation, physical activity.